Global perspectives on social media in tertiary learning and teaching emerging research and opportunities - Piven, Inna 1971-; Gandell, Robyn 1959-; Lee, Maryann 1971-; Simpson, Ann M. (IGI Global, 2018)
"This book reviews important concepts, possible pedagogies and potential educational contexts related to social media use in the higher education classroom. It also looks at the evolving nature of the technologies and practices available in today's teaching and learning context as well as ones that are considered to impact higher educational learning and teaching in the future" ...